Cyclic oculomotor palsy: description of a case and hypothesis of the mechanism. Issue 5 (May 1983) - Bateman, D E; Saunders, M
Abstract : An unusual case of cyclic oculomotor palsy is described where the probable cause was a supraclinoid aneurysm. A mechanism is suggested by which the features of cyclic oculomotor palsy can be explained solely by a peripheral lesion.